Understanding knowledge sharing in the Jordanian construction industry. Issue 3 (13th July 2015) - Arif, Mohammed; Mohammed, Al-Zubi; Gupta, Aman Deep
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop a model to understand and facilitate more knowledge sharing (KS) among construction companies in Jordan. Sixteen cultural variables that affect KS were identified through self-administered questionnaires. Design/methodology/approach – Factor analysis was used to find possible relationships between the cultural variables for grouping purposes and to eliminate the cultural variables that do not affect KS. The results of factor analysis were further refined using a brainstorming session and Analytic Hierarchy Process (AHP) was used to prioritise the factors obtained through the factor analysis. Findings – Trust, management and communication were identified as the three most important factors, whilst communication was acknowledged as the least important factor. Originality/value – This research uses factor analysis and AHP to study the influence of cultural factors on KS. It develops a hierarchy of factors that affect effective KS within the Jordanian context. The paper investigated KS in-depth and highlighted the components that constitute KS in an organisation. Based on extensive literature review, this study found the relative importance of different factors that affect KS. The emphasis on trust was found to be more critical than the presence of a computer-based system. In addition, this is the first paper of this type to look at KS in the context of the Jordanian construction industry.